Lời giải:
a) Ta có: {x_n} = 1 - \frac{1}{{n + 1}} < 1 với mọi n > 0 \Rightarrow {x_n} - 1 < 0 với mọi n > 0.
Do đó, {y_n} = f\left( {{x_n}} \right) = \frac{{\left| {{x_n} - 1} \right|}}{{{x_n} - 1}} = \frac{{ - \left( {{x_n} - 1} \right)}}{{{x_n} - 1}} = - 1.
Ta cũng có: {x'_n} = 1 + \frac{1}{n} > 1 với mọi n > 0 ⇒ x'n – 1 > 0 với mọi n > 0.
Do đó, {y'_n} = f\left( {{{x'}_n}} \right) = \frac{{\left| {{{x'}_n} - 1} \right|}}{{{{x'}_n} - 1}} = \frac{{{{x'}_n} - 1}}{{{{x'}_n} - 1}} = 1.
b) Ta có \mathop {\lim }\limits_{n \to + \infty } {y_n} = \mathop {\lim }\limits_{n \to + \infty } \left( { - 1} \right) = - 1; \mathop {\lim }\limits_{n \to + \infty } {y'_n} = \mathop {\lim }\limits_{n \to + \infty } 1 = 1.
c) Ta có: f\left( x \right) = \frac{{\left| {x - 1} \right|}}{{x - 1}} = \left\{ \begin{array}{l}\frac{{x - 1}}{{x - 1}}\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,n\^e 'u\,\,x - 1 > 0\,\,\,\,\,\\\frac{{ - \left( {x - 1} \right)}}{{x - 1}}\,\,\,\,\,\,\,\,n\^e 'u\,\,x - 1 < 0\end{array} \right. = \left\{ \begin{array}{l}1\,\,\,\,\,\,\,\,n\^e 'u\,\,x - 1 > 0\,\,\,\,\,\\ - 1\,\,\,\,n\^e 'u\,\,x - 1 < 0\end{array} \right.
Vì xn < 1 < x'n, suy ra xn – 1 < 0 và x'n – 1 > 0 với mọi n.
Do đó, f(xn) = – 1 và f(x'n) = 1.
Vậy \mathop {\lim }\limits_{n \to + \infty } f\left( {{x_n}} \right) = – 1 và \mathop {\lim }\limits_{n \to + \infty } f\left( {{{x'}_n}} \right) = 1.